A Delphi Study to Identify Important Factors for Determining the Level of Adherence to ISPS Code Implementation - Aminuddin Md Arof; Ahmad Farhan Awis Khadzi (International Journal of Supply Chain Management, 2018)
The International Ship and Port Facility Security (ISPS) Code was adopted in 2004 as a preventive measure to enhance maritime security in ports and on-board ships. The regulation was made compulsory under Chapter XI-2 of the International Safety of Life at Sea (SOLAS) Convention by International Maritime Organisation (IMO). Since the implementation of the ISPS Code is rather new as compared to other IMO regulations, it is deemed necessary to find out whether employees who work in ports are fully aware and adhere to the requirements of the Code. This research is therefore meant to identify the important determinants to ensure effective implementation of ISPS Code and investigate the level of adherence to ISPS Code implementation amongst Vale Malaysia Minerals (VMM) employees. In this research, the primary data is collected using the Delphi technique. This study concludes that other than those addressed in the literature, two more important factors can be used to determine the implementation of ISPS code and that VMM has been assessed as satisfactorily adhered to the general ISPS Code requirements.